Functionality of R290 Flammable Refrigerant Module - Rozikin, Anis Auni; Yunus, Faizal Amin Nur; Hussin, Azman; Razali, Nizamuddin; Abdul Rahman, Khairul Anuar; Rahim, Mohd Bekri (Research and Innovation in Technical and Vocational Education and Training, 2024)
Less interactive modules can make the learning and teaching process (PdP) have no impact on students. Therefore, the use of teaching aids is an important matter in the learning and teaching process (PdP). Effective ABBM has a good impact where it can launch more learning and teaching sessions in the classroom between teachers and students. The researcher has developed a learning module based on the ADDIE Model. This flammable refrigerant module was developed to reduce student dependence on teachers in delivering learning while in class. The module that has been developed by the researcher is to use a storyboard as a guide in developing this module. Then, the R290 combustible refrigerant module was designed using the Canva website where this module emphasizes aspects of the visual, auditory, and kinesthetic (VAK) learning style. The results of the study found that the developed module is suitable and able to function as an ABBM in the classroom. All three experts agreed that this module is functional with a percentage of 100%.